2013
DOI: 10.1902/jop.2012.120458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maxillary Sinus Membrane Perforation on Vital Bone Formation and Implant Survival: A Retrospective Study

Abstract: The augmented sinuses in this study that exhibited MSMPs that occurred during the SAP (which were treated during surgery) show SS greater vital bone percentages compared with the non-perforated sinus group. There were no SS differences in implant survival in the perforated versus non-perforated groups. In this study, sinus MSMPs, when properly repaired during surgery, do not appear to be an adverse complication in terms of vital bone production or implant survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 14 publications
3
63
0
2
Order By: Relevance
“…A sinus augmentation procedure is an easy and safe procedure with minimal risk of complications. However, one of the possible complications that can occur during surgery is perforation of the Schneiderian membrane . The osteotomy for lateral window sinus access usually performed using the piezosurgery The advantage of piezosurgery to cut the bone window decreasing the risk of Schneiderian membrane perforation .…”
Section: Discussionmentioning
confidence: 99%
“…A sinus augmentation procedure is an easy and safe procedure with minimal risk of complications. However, one of the possible complications that can occur during surgery is perforation of the Schneiderian membrane . The osteotomy for lateral window sinus access usually performed using the piezosurgery The advantage of piezosurgery to cut the bone window decreasing the risk of Schneiderian membrane perforation .…”
Section: Discussionmentioning
confidence: 99%
“…; Froum et al. ). Others, on the contrary, have shown more postoperative complications such as sinusitis, graft failure (Nolan et al.…”
mentioning
confidence: 97%
“…36 It has been reported that bone grafts in block form tend to slow down the process of graft revascularization compared to particulate bone chips that naturally create the space for angiogenesis which is fundamental to successful osteogenesis. 40,41 Nevertheless, the correlation between intrasurgical perforation of the sinus membrane and the occurrence of postoperative complications and negative graft outcomes is controversial in the scientific literature. 38,39 There is no evidence that such intraoperative complication compromises the success of the treatment nor that it is related to an increased implant failure rate.…”
Section: Discussionmentioning
confidence: 99%